Post graduate students insights into understanding intercultural communication in global workplaces - Yusof, Norhafezah; Kaur, Amrita; Cheah, Joyce Lynn-Sze (Routledge, 2019)
Effective Intercultural communication competencies (ICC) are central to professional success. However, despite this emphasis several graduates remain poorly prepared to demonstrate these attributes and skills. Pedagogical innovations that are grounded in theoretical framework of teaching and learning and communication principles have the potential to yield meaningful learning experiences for students. This article draws on a term long qualitative study conducted under the scholarship of teaching and learning (SoTL) inquiry that exposed post graduate students to real life interactions at global workplaces to construe their own meaning of ICC. The findings discuss pedagogical implications for the practitioners of communication education in higher education.